Responsibility of Marketplaces and Business Actors for the Sale of Fake Herbal Medicines from the Perspective of Consumer Protection - Hidayat, Muhammad Rahmadzani; Hutabarat, Sylvana Murni Deborah (Al-Risalah, 2026)
The rapid expansion of e-commerce has significantly increased the distribution of herbal medicines, yet it has simultaneously facilitated the circulation of counterfeit products that jeopardize consumer safety and lack mandatory health permits. This phenomenon highlights a critical legal gap where the ease of marketplace transactions allows sub-standard and hazardous medicines to bypass rigorous safety standards, necessitating a clear definition of liability for both sellers and platform providers. This research employs a normative juridical method utilizing statutory and case study approaches to analyze existing legal frameworks, specifically Law Number 8 of 1999 on Consumer Protection and BPSK Decision Number 001/PNTP/BPSK-DKI/I/2025. The study reveals that marketplaces, alongside business actors, bear shared legal liability under the principle of strict liability, as platforms derive economic benefit from these transactions and are obligated as electronic system providers to ensure the security of the managed trading system. Furthermore, while the Consumer Dispute Resolution Board (BPSK) provides a mechanism for redress, its current considerations focus primarily on achieving consensus through mediation rather than conducting deep normative testing or enforcing strict sanctions for violations of consumer protection laws.